Sew lingerie : make size-inclusive bras, panties, swimwear & more : everything you need to know - Kulig, Maddie, 1987- (Stash Books, an imprint of C&T Publishing, 2023)
"In Sew Lingerie, learn the foundations of DIY lingerie, swimwear, and activewear--from the history of lingerie, types of styles, and different fabrics and elastics, to determining your size and making your own garments. Transform your top drawer with affordable, size-inclusive lingerie, swimwear, and activewear that is made just for you"--